2015
DOI: 10.1097/aco.0000000000000154
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in cardiac surgery

Abstract: Although there has been much high-quality research conducted in this field in recent years, preventing CSA-AKI by avoiding renal insults remains the mainstay of management. Although biomarkers have the potential to diagnose CSA-AKI at an earlier stage, efficacious interventions to treat established CSA-AKI remain elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 79 publications
(64 reference statements)
2
61
0
4
Order By: Relevance
“…The incidence of AKI in the score development population and in validation cohort was 16.9% and 15.7%, respectively, which is congruent with previous reports where the incidence of AKI ranged from 5% to 40% [4,9,16]. Three predictive models for CSA-AKI risk not requiring RRT have been developed so far: NNECDSG [8], MCSPI [7], and AKICS [9].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The incidence of AKI in the score development population and in validation cohort was 16.9% and 15.7%, respectively, which is congruent with previous reports where the incidence of AKI ranged from 5% to 40% [4,9,16]. Three predictive models for CSA-AKI risk not requiring RRT have been developed so far: NNECDSG [8], MCSPI [7], and AKICS [9].…”
Section: Discussionsupporting
confidence: 68%
“…However, these markers are not widely available in routine practice, and further studies must be developed to extend its use. Neutrophil gelatinase-associated lipocalin is one of the most up-regulated genes and proteins early after AKI and one of the most studied novel biomarkers in the early detection of AKI [16]. Several authors [27,28] have studied the role of NGAL in predicting CSA-AKI and have demonstrated better and earlier predictive power as compared to creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Progress has been made during the last years on the definition of the syndrome [i.e., Kidney Disease Improving Global Outcome (KDIGO) criteria, (5)], on better understanding of its pathophysiology, and on the identification of earlier severity stages (6). It is now clear that cardiac surgery associated AKI (CSA-AKI) has a multifactorial origin since different pathways simultaneously affect renal function: patients' pre-operative susceptibility, exogenous and endogenous toxins, metabolic factors, hemodynamic instability, ischemia/reperfusion injury, microembolization, neurohormonal activation, endothelial cells and renal epithelial cells activation, and release of inflammatory mediators and oxidative stress (7)(8)(9). Inflammation, deriving from several pathways, plays a key role in CSA-AKI: cardiopulmonary bypass and its contact activated response, aortic cross-clamp and circulatory arrest, tissue hypoxia, and transfusions co-act leading to a systemic inflammatory response syndrome (7,(10)(11)(12).…”
mentioning
confidence: 99%
“…It is now clear that cardiac surgery associated AKI (CSA-AKI) has a multifactorial origin since different pathways simultaneously affect renal function: patients' pre-operative susceptibility, exogenous and endogenous toxins, metabolic factors, hemodynamic instability, ischemia/reperfusion injury, microembolization, neurohormonal activation, endothelial cells and renal epithelial cells activation, and release of inflammatory mediators and oxidative stress (7)(8)(9). Inflammation, deriving from several pathways, plays a key role in CSA-AKI: cardiopulmonary bypass and its contact activated response, aortic cross-clamp and circulatory arrest, tissue hypoxia, and transfusions co-act leading to a systemic inflammatory response syndrome (7,(10)(11)(12). In light of these aspects, many strategical and therapeutic approaches have been attempted in order to limit the occurrence of AKI after cardiac surgery (13).…”
mentioning
confidence: 99%
“…Acute kidney injury (AKI) is a well-known, frequent complication in patients after cardiac surgery, occurring in 7% to 40%, depending on its definition (1). Subsequently, it is independently associated with substantial morbidity [such as need for renal replacement therapy, longer length of hospital stay and progression of chronic kidney disease (CKD)] and mortality (2).…”
mentioning
confidence: 99%